Literature Review of Fuzzy Set Theory: Applications and Methodologies - Mohammed, Mohammed Jasim (Journal of Economics and Administrative Sciences, 2025)
This paper represents a comprehensive literature survey of the research published in the Journal of Economics and Administrative Sciences (JEAS) on applications and methodologies of fuzzy set theory. The review traced how fuzzy logic has been evolving in decision-making, optimization, and modeling uncertainties in published articles such as economics, management, and engineering. The categorization of fuzzy methodologies into various domains such as fuzzy linear programming, fuzzy regression, fuzzy control systems, and fuzzy multi-criteria decision-making relies heavily on the study of existing research. An analysis revealed an increasing trend of investigations highlighting the interplay of fuzzy logic with artificial intelligence, statistical modeling, and heuristic optimization methods. The developments in methodologies of fuzzy decision-making frameworks are again examined from the perspective of applicability in real-life problem situations involving imprecise and uncertain data. Findings that fuzzy logic, therefore, contributed considerably to the enhancement of problem-solving in economics and administrative sciences through more flexible and adaptive models. Therefore, this literature review will be an excellent guide for researchers in fuzzy set theory applications to grasp existing gaps and suggest future directions for improving fuzzy methodologies across industries.